Subjective experience of mental states in conditions of family deprivation - A.I. Ahmetzyanova; L.V. Artishcheva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The development of mental states of orphaned children brought up in institutionalized institutions has been discussed. The purpose of the paper is to analyze the specifics of the course of mental states in adolescents living in family deprivation conditions. This problem is relevant, because the experience of mental states plays an important role in the process of adaptation and socialization of children, in the development of communication and interaction skills, in personal development, and in emotional-volitional sphere formation. The content of subjective experience of such mental states as joy and sadness has been defined. The main method in the study of this problem is the method of content analysis of subjects’ self-reports. The subjects of the study are adolescents raised in orphanages. The study has been carried out in two stages: description of mental states in the past future. We have identified the content of experience of mental states of joy and sadness, which includes the manifestations of the mental (expression, emotional processes, behavioral manifestations, value-semantic sphere), as well as external factors (events, situations, actions of significant adults). It has been shown that the experience is characterized by poverty and a small coverage of used mental states characteristics and by the stinginess of the content.